Interindustry Estimation of General Price-Level Impact on Financial Information: More Data and a Reply. - Petersen, Russell J. (The Accounting Review, 1978)
The article presents a reply to the comments made by authors S. Basu and J.R. Hanna (BH), on the author's article related to interindustry estimation of general price-level impact on financial information. The purpose of the present correspondence is to discuss the essential experimental and conceptual issues which seem to be at the center of the concern indicated by BH, and to add additional data and analysis to that now existing in the literature of general price-level research in accounting. The essence of the criticisms leveled at the author's earlier work is as follows, an "error" was committed in the presentation and analysis of the restated data which was caused by comparing restated and rolled forward with data measured on a basic historical cost basis. An error was committed in the calculation of the standard normal variates, and that the method employed to analyze the data was not the best selection in the circumstances. The issues of deciding the best way to prepare and present data to illustrate the effects of changing a measurement rule in accounting are subtle.